2013
DOI: 10.4049/jimmunol.1300104
|View full text |Cite
|
Sign up to set email alerts
|

Functional KCa3.1 Channels Regulate Steroid Insensitivity in Bronchial Smooth Muscle Cells

Abstract: Identifying the factors responsible for relative glucocorticosteroid (GC) resistance present in patients with severe asthma and finding tools to reverse it are of paramount importance. In asthma there is in vivo evidence of GC-resistant pathways in airway smooth muscle (ASM) bundles which can be modelled in vitro by exposing cultured ASM cells to TNFα/IFNγ. This drives GC insensitivity via protein phosphatase-5 (PP5)-dependent impairment of GC receptor (GR) phosphorylation. Here, we investigated whether KCa3.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 68 publications
3
34
0
Order By: Relevance
“…We have previously reported that ASM cells exposed to TNF-a/IFN-g combination become refractory to the antiinflammatory action of corticosteroids (23,25,29,32,33 (19,20), and experimental autoimmune neuritis (17). These studies highlighted the lack of typical side effects associated with GC treatment and the equal efficacy of CpdA when compared with dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that ASM cells exposed to TNF-a/IFN-g combination become refractory to the antiinflammatory action of corticosteroids (23,25,29,32,33 (19,20), and experimental autoimmune neuritis (17). These studies highlighted the lack of typical side effects associated with GC treatment and the equal efficacy of CpdA when compared with dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of CX3CL1, CXCL10, and CCL5 in the supernatants were measured as described previously (23).…”
Section: Elisamentioning
confidence: 99%
See 1 more Smart Citation
“…K Ca 3.1 is expressed widely in the airways of both healthy controls and people with asthma (Arthur et al, ; Chachi et al, ). Immunostaining is evident in the airway epithelial cells, goblet cells, airway smooth muscle cells, airway fibroblasts, submucosal glands, inflammatory cells and endothelial cells (Arthur et al, ; Chachi et al, ).…”
Section: Kca31 In Fibrosismentioning
confidence: 99%
“…K Ca 3.1 is expressed widely in the airways of both healthy controls and people with asthma (Arthur et al, ; Chachi et al, ). Immunostaining is evident in the airway epithelial cells, goblet cells, airway smooth muscle cells, airway fibroblasts, submucosal glands, inflammatory cells and endothelial cells (Arthur et al, ; Chachi et al, ). Functional K Ca 3.1 channels are also expressed by cultured primary human airway epithelial cells and airway smooth muscle cells (Arthur et al, ; Shepherd et al, ).…”
Section: Kca31 In Fibrosismentioning
confidence: 99%